Pemanfaatan Teknologi Informasi untuk Pengelolaan Sumber Daya Alam Berkelanjutan di Desa Bonto Masunggu Kabupaten Bone Sulawesi Selatan - Jumiati Syam; Faridah Faridah; Thanwain Thanwain (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This research aims to evaluate the use of information technology in managing natural resources in Bonto Masunggu Village, Bone Regency, South Sulawesi. This village is known to have abundant natural resource potential, including the agricultural, fisheries and forestry sectors. However, natural resource management in this village faces significant challenges caused by limited access to technology and low digital literacy among the community. The research method used is a qualitative approach involving in-depth interviews, field observations and documentation studies. Research findings reveal that although information technology has great potential to improve sustainable management of natural resources, its implementation in Bonto Masunggu Village is still hampered by several factors. The main factors identified are people's low knowledge and skills in using information technology, as well as inadequate infrastructure, such as limited internet networks and technological devices. Information technology, including weather monitoring applications, geographic information systems (GIS), and environmental sensors, can provide significant solutions to improve the efficiency and effectiveness of natural resource management. However, to maximize the benefits of this technology, comprehensive training programs, better infrastructure development, and policy support that supports technology adoption are needed. This research also underlines the importance of collaboration between village governments, non-governmental organizations and the private sector in supporting the implementation of information technology. It is hoped that the results of this research will provide insight and practical recommendations that can be applied in other villages in Indonesia, as well as contribute to efforts to manage natural resources more sustainably and effectively at the national level